The relationship between nutritional status and fall risk assessed by timed up and go test in elderly in the primary care network of Bang Kruai hospital: a cross-sectional study - Pavananont, Pornvipa; Phithakwongrojn, Kod; Bosittipichet, Tatree; Leesri, Thanakamon (International Journal Of Community Medicine And Public Health, 2025)
Background: Malnutrition and falling problems are common and important in older adults. The previous study found that malnutrition was associated with falling in older adults. Studies of the relationship between these two conditions are limited and there have been limited data about risk of malnutrition in primary care of Thailand, so we investigate the relationship of malnutrition, risk of malnutrition and risk of falling in older patients. Methods: The study was cross-sectional analytic study of 224 participants aged 60 years or older who visited the primary care of Bang Kruai Hospital during February to March 2024. Face-to-face interview and test were conducted. The nutritional status was evaluated by using the mini nutritional assessment (MNA). The risk of falling was evaluated by time up and go test. The data were obtained for the prevalence using percentage values. The relationship was analysed by using multivariable logistic regression Results: Among 224 patients with mean age 69.29±6.44 years old, 64.29% of them were women. The prevalence of malnutrition and risk of malnutrition were 3.12 and 30.36%, respectively. The prevalence of risk of falling was 26.79%. This study showed that the malnutrition and risk of malnutrition were significantly associated with risk of falling (Adjusted OR 2.23, 95%CI 1.19-4.22, p<0.001). Conclusions: The malnutrition and risk of malnutrition were related with risk of falling. Therefore, when evaluating an older patient with risk of falling, nutritional status should be evaluated, or risk of falling should also be evaluated in an older patient with risk of malnutrition. Thus, the more comprehensive management of these two problems can be possible.